Temporomandibular Joint Dysfunction Syndrome associated with Betel Nut Chewing: A Clinical Study - Nawaz, Mohammad Khaja Khalid; Sivaraman, GS; Krishnamoorthy, Santham; Balaji, Selva (Journal of Orofacial Research, 2015)
Background: The clinical course of temporomandibular joint (TMJ) dysfunction syndrome was studied among 100 patients between the age of 20 and 50 years. Clicking and pre auricular pain appeared to be the predominant symptom in all age groups. The findings of the study revealed that most of all the patientshad a generalized attrition, generalized stains, and the occurrence of pain dysfunction syndrome (PDS). The chewing habit of betel nut in this place is different from the rest of India. In this place, people chew the hardest form of betel nut. Aims: The aim of this study is to create awareness among people regarding betel nut chewing and its associated TMJ problems. Materials and methods: This study was conducted at the Department of Oral and Maxillofacial Surgery of Dr. H Gordon Roberts Hospital, East Khasi Hills, Shillong, Meghalaya, India. The study consisted of 100 patients. All the patients were subjected to a clinical examination. Results: Prolonged duration of betel nut chewing will cause the masticatory forces to be transmitted to the TMJ and subsequently causes temporomandibular joint dysfunction syndrome. Conclusion: Prolonged betel nut chewing may give rise to TMJ dysfunction syndrome. The consistency of the betel nut also plays a major role in temporomandibular joint dysfunction syndrome. Clicking and preauricular pain appeared to be the predominant symptoms for all age groups. The incidence was higher in females than in males.